(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Basic primitives in AutoCAD graphic software. Analytical methods for designing complex primitives and drawings. Stages of the design process. The design workflow. Creating a flat-contour part drawing in AutoCAD graphic software. Rotating, moving, mirroring, and stretching objects. Constructing objects in AutoCAD graphic software. Creating sections, extrusions, attachments, adding dimensions, and applying scales to objects. Constructing objects using editing tools in AutoCAD graphic software.